2014
DOI: 10.1093/gerona/glu067
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Muscle TLR4 Expression and Metabolic Endotoxemia in Human Aging

Abstract: Aging is associated with alterations in glucose metabolism and sarcopenia that jointly contribute to a higher risk of developing type 2 diabetes. Because aging is considered as a state of low-grade inflammation, in this study we examined whether older, healthy (lean, community-dwelling) participants have altered signaling flux through toll-like receptor 4 (TLR4), a key mediator of innate and adaptive immune responses. We also examined whether a 4-month aerobic exercise program would have an anti-inflammatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
104
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 75 publications
4
104
1
2
Order By: Relevance
“…However, Rodriguez-Miguelez et al reported that TLR4 levels dropped 50 % in overweight, older participants following a low-intensity vibration-platform-based exercise intervention. In the study by Ghosh et al (Ghosh et al, 2014), circulating LBP-1 concentrations were close to double those in young people, as were muscle TLR4 receptor levels. In our study of vervet monkeys, increased LBP-1 levels per se were not associated with age, but the combination of being old and sedentary resulted in ninefold greater LBP-1 concentrations.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…However, Rodriguez-Miguelez et al reported that TLR4 levels dropped 50 % in overweight, older participants following a low-intensity vibration-platform-based exercise intervention. In the study by Ghosh et al (Ghosh et al, 2014), circulating LBP-1 concentrations were close to double those in young people, as were muscle TLR4 receptor levels. In our study of vervet monkeys, increased LBP-1 levels per se were not associated with age, but the combination of being old and sedentary resulted in ninefold greater LBP-1 concentrations.…”
Section: Discussionmentioning
confidence: 69%
“…Intestinal Bleakiness^occurs with advancing age across many species (Ma et al, 1992;Rera et al, 2012;Tran and Greenwood-Van Meerveld, 2013;Ghosh et al, 2014), but only recently has become recognized as an important mediator of healthspan, lifespan, and insulin signaling in invertebrates (Rera et al, 2012;Ulgherait et al, 2014). A Bleaky^mucosa allows greater translocation of microbial antigens into the intestinal wall and portal circulation, inciting inflammation both locally and remotely.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations